The impact of rhino poaching on the accountability disclosures of a state-funded conservation organisation - Barry Ackers (Responsibility and Sustainability, 2024)
The unprecedented growth in the illegal wildlife trade has created a serious challenge for conservation in Africa. Governments around the world often create entities to protect species and preserve biodiversity in their respective countries. Despite numerous interventions to conserve the world’s threatened rhino populations and reduce incidents of rhino poaching, poaching of the world’s rhino populations continue, especially in South Africa. Descriptive and inferential statistics are used to analyze and compare rhino-related disclosures with rhino poaching trends, to identify possible correlations between incidents of rhino poaching and rhino-related, and to establish differences between the periods between 2006 to 2015 (covered in Ackers, 2019) and the subsequent period from 2016 to 2021. Unlike the period from 2006 to 2015 where several rhino-related keywords were strongly correlated with rhino poaching incidents, no correlations were detected from 2016 to 2021. Although incidents of rhino poaching decreased, SANParks appear to have strategically increased its anti-poaching advocacy by retaining high levels of disclosures about rhino-related issues, demonstrating how it has discharged its biodiversity-related mandate. Using the same mixed-methods research approach and similar data, this paper extends the Ackers (2019) study, which examined how South African National Parks (SANParks), by including the disclosures from 2016 to 2021.